Extensive Epidermal Skin Loss Secondary to HSV Type One: Neonatal Management Challenges - Rebecca J Calthorpe; Emma Spencer; Jane C Ravenscroft; Ting S Tang; Anna E Martinez; Anjum Deorukhkar (Case Reports in Pediatrics)
We describe a rare case of a preterm neonate presenting at birth with extensive epidermal skin loss of over 90% due to disseminated herpes simplex virus type one infection. Differential diagnosis included aplasia cutis and epidermolysis bullosa. Serum PCR and mouth swabs confirmed HSV type one, and the patient required three weeks of treatment with intravenous aciclovir, followed by oral aciclovir. We describe the management challenges and give practical solutions applicable to the care of a neonate presenting with widespread skin loss due to any aetiology.